Theoretical Study of Shell-and-Tube Heat Exchanger Effectiveness on Batch Drying of Sawdust Utilizing Waste Heat from Organic Rankine Cycle - Yahdi, M. Arief; Hartulistiyoso, Edy; Yulianto, Muhamad (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Steam power plant has flue gas that are generally discharged into environment. The exhaust gases from internal combustion contain thermal energy that can be utilized for drying processes, which can enhance the energy efficiency of the Organic Rankine Cycle (ORC) system. This research focuses on the use of waste heat for drying applications through heat exchangers. The objective of this work is to study the performance of shell-and-tube type heat exchanger in utilizing waste heat from an ORC system for drying applications. Experimental data was obtained by varying the air velocity of the dryer to validate the numerical simulations. The results showed that increasing air velocity in the heat exchanger caused a decrease in heat exchanger outlet temperature, water vapor mass, and heat exchanger effectiveness. The decrease in these parameters reduces heat transfer required for drying, so water mass rate of material decreases and drying time gets longer. Validation of simulation and experiment data for outlet heat exchanger temperature was determined by MAPE value of less than 20% which means good prediction model. Keywords: Air velocity, Drying, Effectiveness heat exchanger, Exhaust gas, Heat exchanger.